2019
DOI: 10.1016/j.jclepro.2018.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Model development of sustainability assessment from a life cycle perspective: A case study on waste management systems in China

Abstract: Due to the problems of municipal solid waste (MSW) during the expanding urbanization, strategy to find an environmentally friendly, energy efficient, cost-effective, and socially acceptable MSW management system is essential for sustainable development. This study establishes a novel environment-energyeconomy-society (3E þ S) model from a life cycle perspective for sustainability assessment: life cycle assessment for evaluating environmental performance and energy consumption, life cycle costing for recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Despite the numerous frameworks proposed in the literature, data collection challenges and possible other factors have limited the number of analytical studies (to the best of our knowledge: Gabbay de Souza et al., 2016 , Zijp et al., 2017 , Millward-Hopkins et al., 2018 , Di Maria and Sisani, 2019 , Stone et al. 2019 , and Zhou et al., 2019 ). Moreover, for the specific case of household and/or municipal food waste, no such studies are available.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous frameworks proposed in the literature, data collection challenges and possible other factors have limited the number of analytical studies (to the best of our knowledge: Gabbay de Souza et al., 2016 , Zijp et al., 2017 , Millward-Hopkins et al., 2018 , Di Maria and Sisani, 2019 , Stone et al. 2019 , and Zhou et al., 2019 ). Moreover, for the specific case of household and/or municipal food waste, no such studies are available.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies are carrying a novel environment-energy-economy-society (3E + S) model from a life cycle perspective for sustainability assessment. As a sample of them, Zhou [17] has shown that incineration was the best choice in his study and landfill with and without energy recovery rank the third and the last position in China.…”
Section: Several Scientific Approaches Worldwidementioning
confidence: 99%
“…The lifecycle and handling of municipal waste are dealt with in other works [30][31][32][33][34][35]. Case studies related to the assessment of the waste management lifecycle are presented in previous studies [32,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…The lifecycle and handling of municipal waste are dealt with in other works [30][31][32][33][34][35]. Case studies related to the assessment of the waste management lifecycle are presented in previous studies [32,33,35]. For example, one study [32] focuses on the assessment of the sustainability of China's waste management system, while another [33] on the lifecycle of plastics in India, and a third [35] on general municipal solid waste in Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation